Hemodialysis catheter-associated superior vena cava syndrome and pulmonary embolism: a case report and review of the literature. (December 2016) - Thapa, Sritika; Terry, Peter; Kamdar, Biren
Abstract Background Hemodialysis (HD) catheters are frequently inserted into the superior vena cava (SVC), and can lead to thrombotic complications. However, to our knowledge, HD catheter-related thrombosis leading to subsequent SVC syndrome, bacteremia, and pulmonary emboli has not been described. Case presentation A 28-year-old dialysis-dependent woman with IgA nephropathy developed facial swelling, head pressure, headache, nausea, dizziness and fever 6 weeks after right internal jugular (IJ) HD catheter placement. Chest and neck imaging demonstrated a non-occlusive thrombus surrounding the HD catheter and extending from the SVC to the junction of the right IJ and right subclavian veins, confirming thrombosis-associated SVC syndrome. Intravenous (IV) anticoagulation was initiated, as well as IV vancomycin forStaphylococcus epidermidis bacteremia. Despite prompt intravenous anticoagulation, 9 and 12 days after initial presentation she developed catheter-associated pulmonary embolism (PE) and PE-associated pulmonary infarction, respectively. Hypercoagulable workup was negative. The HD catheter was eventually replaced, HD resumed, and the patient was transitioned from intravenous to oral anticoagulation and discharged. Nine months later, she underwent successful renal transplantation. Conclusion SVC syndrome and pulmonary embolism are potential consequences of HD catheter-related thrombosis. Given the frequency of HD catheter placement, physicians should be aware of these potential complications in any patient with HD catheter-related thrombosis.